The Relationship between Mothers' Knowledge and Parenting Patterns with the Nutritional Status of Toddlers in the Gunung Puskesmas Work Area - Diana (International Journal of Medicine And publich Health, 2025)
Nutrition is a crucial element in the body. Good nutrition keeps the body fit and allows for optimal activity. Therefore, parents must understand their children's nutritional needs to prevent malnutrition. Nutrition is a crucial factor in determining human health and well-being. A person's nutritional status is considered good when there is a balance and harmony between their physical and mental development. Optimal nutritional status is achieved when optimal nutritional needs are met. This study used an analytical survey method, with a cross-sectional approach (Chi-square), where the analytical survey involved both independent and dependent variables. The sampling technique for this study was accidental sampling, which is a method of sampling by chance encounters. The population in this study were toddlers in the working area of ​​the Gunung Tua Community Health Center, Panyabungan District, Mandailing Natal Regency in 2025. The results of statistical tests using the chi square test showed a significant relationship (P = 0.000 < 0.05) so that it can be concluded that there is a relationship between maternal parenting patterns and the nutritional status of toddlers in the working area of ​​the Gunung Tua Community Health Center, Panyabungan District in 2025.